Ang Teacher ko ay Mamaw: A Children’s Animated Story Book on Understanding a Teacher’s Love - Sanding , Mervin (International Journal of Sustainability and Advanced Integrated Research, 2026)
Teachers play a significant role in shaping students’ academic, social, and emotional development. However, in early educational settings, students may misinterpret teachers’ disciplinary actions as signs of anger, harshness, or lack of care. Such misconceptions can create fear and distance in the teacher–student relationship, thereby affecting communication, trust, and classroom engagement. In response to this concern, the present study developed Ang Teacher Ko ay Mamaw: A Children’s Animated Story Book on Understanding a Teacher’s Love, a digital storybook intended to help young learners understand the caring intentions behind teacher discipline and guidance. The study employed a quantitative descriptive-evaluative research design. Using random sampling, 30 elementary teachers handling Grade 1 to Grade 3 pupils from public and private schools were selected as respondents. Data were collected through a survey questionnaire consisting of closed-ended questions and five-point Likert-scale evaluation items. Frequency, percentage, and mean were used to analyze the data. The results showed that the most common misconception identified by the respondents was that teachers easily get angry (63.30%). The respondents also indicated that what they most wanted students to understand was that teachers love their students in different ways (63.30%). In the evaluation of the digital storybook, the aesthetic dimension obtained an overall mean of 4.51, interpreted as Highly Satisfied, while the content dimension obtained an overall mean of 4.35, interpreted as Very Satisfied. These findings indicated that the storybook was visually appealing, educationally meaningful, and effective in communicating its intended message. The study concluded that the digital storybook was a suitable and effective material for helping children better understand teachers’ behavior and intentions. It also demonstrated the potential of visual storytelling as a tool for promoting empathy, strengthening teacher–student relationships, and supporting positive learning environments in early education.
Keywords: digital storybook, teacher–student relationship, children’s literature, visual learning, teacher perceptions, early childhood education, educational media